Assessing the adaptability of agronomic landscape to climate change at watershed scale - Qiu, R.; Zheng, H. (Elsevier, 2025)
CONTEXT: A region's agricultural practices, particularly farmers' choices regarding plowing and planting, influence the adaptability of croplands to climate change. However, the role of these agronomic landscapes in mediating cropland responses to diverse climate conditions remains unclear. OBJECTIVE: This study evaluates a typical watershed in Northeast China. We continuously tracked shifts in crop distribution patterns and associated field yield to determine how agronomic landscapes impacted cropland productivity during both dry and wet years. METHODS: Object-oriented methods were employed to extract field boundaries in a representative sub-watershed. We mapped agronomic landscape patterns based on the following elements: crop type, landscape position, and ridge direction. We then compared field productivity, as measured by the Normalized Difference Vegetation Index (NDVI), across various agronomic landscapes and climatic years from 2016 to 2023. RESULTS AND CONCLUSIONS: Our findings indicate that cropland productivity is associated with agronomic landscapes. Maize productivity demonstrated an increasing trend from low to high landscape positions; whereas, soybean productivity peaked at medium positions and was lowest in uphill and downhill locations. Specifically, agronomic landscapes reflected by cross ridges at the toeslope exhibited the lowest productivity for both maize and soybeans. In addition, landscapes incorporating soybeans demonstrated greater adaptability to varying weather conditions compared to those dominated by maize. During wet years, landscapes with maize situated in the footslope with strike ridges exhibited higher productivity. In contrast, landscapes incorporating soybeans displayed robust productivity across most landscape positions, particularly in the toeslope with strike ridges. During dry years, landscapes featuring maize in both the footslope with strike ridges and the toeslope with cross ridges demonstrated greater productivity. Similarly, landscapes with soybeans distributed throughout the watershed, especially in the footslope with cross ridges and toeslope with strike ridges, exhibited higher yields. SIGNIFICANCE: Our findings highlight the crucial role of optimizing agronomic landscapes to enhance the climate resilience of croplands and ensure stable yields. It is thus suggested that the implementation of crop sequences and their spatial arrangement in watersheds should be prioritized to lessen the adverse effects of climate change.